Gestão da inovação no setor público: acumulação de capacidades tecnológicas e os processos subjacentes de aprendizagem: evidências da Secretaria do Tesouro Nacional do Brasil durante o período de 1986 a 2005 - Oliveira, Paulo de Tarso Campolina (2012)
This thesis studies the implications of learning processes in the accumulation of technological capabilities within the National Treasury Secretariat – STN, an agency of the Ministry of Finance of Brazil, during the period between 1986 and 2005. It aims to expand studies in the field of Innovation in the Public Sector. With this goal, the analytical frameworks of Figueiredo (2009) and Bell and Pavitt (1995) developed to investigate cases of accumulation of technological capabilities in the Private Sector were adapted. Following these frameworks, based on evidence collected in documentary research and observation, learning processes related to the acquisition and conversion of knowledge, were examined based on two key features: variety and intensity; and accumulation of skills was studied based on four pre-established technology functions. From the analysis conducted, it was observed a relationship between increasing use of learning mechanisms and improvement of technological capabilities in the ambit of the STN. The accumulation and improvement of technological capabilities occurred at different speeds, reaching advanced level in 5, 7,10, and 12 years respectively in the functions of: 'Financial Management', 'Federal Management', 'Institutional Management' and 'Debt Management'. Observing, from this level, the development of innovative capabilities. Corroborating conclusions reached in previous studies conducted in private organizations, this research shows that learning processes fostered significant changes in the STN, making possible an accumulation of technological capabilities, especially after the institutional area of the Secretariat was strenghened – during 1995. Therefore, to emphasize the implications of learning processes in the accumulation of technological capabilities within the STN, this study can contribute to reducing the gap between the volumes of works related to corporate innovation and innovation in the public sector, it is reasonable to assume that conclusions reached herein may be useful to the activities of public managers, policymakers, scholars of public administration, among other social actors.